MOTIVATION OF RAW MILK CONSUMPTION AMONG MALAYSIANS - Nuraini Mahror; Nursyuhada Azzman; Noor Hazarina Nordin; Suraya Sulaiman; Mohd Ikhmal Hanif Abdul Khalid (Journal of Islamic, Social, Economics and Development, 2020)
Raw or unpasteurized milk is rich with beneficial nutrients including calcium,potassium, phosphorus and vitamins. Recently, there was a tremendous demand for raw milkin the local market. However, consumption of raw milk is risky as it commonly associated withfood born disease outbreaks. Therefore, this study aimed to identify the motivations forunpasteurized milk consumption among Malaysians. A total of 180 respondents hadparticipated in this survey and a questionnaire was distributed via social media. The resultrevealed that majority of the consumers were female, Malay, aged between 21 to 30 years old,a bachelor degree holder and were living in an urban area. The motivation for raw milkconsumption was dominated by the belief that raw milk possesses holistic health benefitsfollowed by taste, prevention of immune-related disease, support for local farm and the beliefthat processed milk is not safe. The consumers had moderate knowledge about the healthbenefits and health risks associated with raw milk (M=3.30, SD=1.048). However, the majorityof respondents weren’t aware that selling raw milk is illegal in Malaysia. There was nosignificant difference between male and female consumers’ perception regarding healthbenefits and health risk associated with raw milk (t=1.637, df= 69.037, p-value 0.11). Theperceptions of the consumers between urban, sub-urban and rural areas also showed nosignificant difference F(1.064) = 0.35 at 95% confident interval.